Difelikefalin in the treatment of hemodialysis patients with pruritus: a systematic review and meta-analysis - Cai, Xiaoyue; Wu, Guiming; Lin, Yan; Yang, Lichuan (Frontiers in Pharmacology, 2024)
Background and Objective: Uremic pruritus is a persistent condition that is difficult to cure in patients with end-stage renal disease who are having regular dialysis. It is highly prevalent, and current therapies have limited effectiveness and can cause significant adverse effects. Several trials have provided evidence that difelikefalin can be an effective treatment for uremic pruritus, with few side responses. However, it is important to note that the available evidence is limited. This study collected published randomized controlled trials for systematic review and Meta-analysis, to explore the efficacy and safety of difelikefalin treating uremic pruritus and to provide evidence-based medical evidence for clinical treatment. Methods: A systematic literature search was conducted in PubMed, EMBASE, Web of Science, the Cochrane Library Data from building libraries to 6 January 2024. We extracted data from eligible studies to analyze the efficacy and safety of difelikefalin in the treatment of hemodialysis patients with pruritus. Results: This study comprised 9 trials with 4,118 people. The meta-analysis demonstrated that difelikefalin is more effective than placebo in treating uremic pruritus. Specifically, difelikefalin resulted in a greater improvement in WI-NRS scores of at least 3 points from baseline (OR = 1.98) and at least 4 points from baseline (OR = 1.94). Additionally, difelikefalin led to a decrease in the total score of the 5-D itch scale (MD = 1.56), a decrease in the skindex-10 scale score (MD = 4.92), and a decrease in the WI-NRS scale score (MD = 0.91). Conclusions Difelikefalin demonstrates significant efficacy in alleviating pruritus in individuals suffering from uremia.Althogh it has adverse events, they are mild.